HUBUNGAN IKLIM KELAS DAN MOTIVASI BELAJAR DENGAN HASIL BELAJAR PESERTA DIDIK - Bradley Setiyadi; Lucia Loviansi (Universitas Pakuan, 2020)
THE RELATIONSHIP BETWEEN CLASSROOM CLIMATE AND LEARNING MOTIVATION WITH STUDENT LEARNING OUTCOMESThis study aims to look at the relationship between classroom climate and learning motivation with student learning outcomes in Class XI Office Administration at SMK Negeri 1 Kota Jambi. This study uses quantitative methods with ex post facto design. The population used in this study were students of Class XI Office Administration at SMK Negeri 1 Kota Jambi. The study population was 122 students and the sample chosen was 67 students based on intrapolation calculations and then the distribution of samples using Simple Random Sampling. Data collection techniques in this study used primary data in the form of a questionnaire and secondary data in the form of data on the average value of student tests. Data analysis techniques used in this study are simple correlation analysis and multiple correlation analysis. The results showed that: (1) There was a relationship between classroom climate and student learning outcomes of 0.595 with a percentage of 59.5% and a significance value of 0.000 so that rcount rtable or 0.595 0.201 could be said to be significant. Because r count r table then Ho is rejected and Ha is accepted. (2) There is a relationship of learning motivation with student learning outcomes of 0.744 with a percentage of 74.4% and a significance value of 0.000 so that rcount rtable or 0.744 0.201 can be said to be significant. Because r count r table then Ho is rejected and Ha is accepted; and (3) There is a relationship between classroom climate and learning motivation with student learning outcomes of 0.783 with a percentage of 78.3%. It can be concluded that classroom climate and learning motivation together have a correlation with student learning outcomes. This conclusion suggests that educators can optimize classrooms and provide awareness of the importance of learning and motivate students during the learning process, by creating a conducive classroom atmosphere and providing interesting learning methods so that students do not feel bored and bored, and feel safe and comfortable and excited in learning in class so that it will have implications for maximum learning outcomes.